KAJIAN MAKNA SIMBOL - SIMBOL DALAM UPACARA PERKAWINAN SUNDA DI KEC. PANJALU KAB. CIAMIS DAN RELEVANSINYA TERHADAP PEMBENTUKAN KELUARGA SAKINAH - Syarif, Ahmad; Muhammad Abduh (Program Studi Hukum Keluarga Islam, 2025)
This research aims to examine the philosophical meanings of symbols in the Sundanese traditional wedding ceremony in Panjalu District and to analyze their relevance to the establishment of a sakinah family. Sundanese wedding traditions are rich with symbolic expressions that are not merely cultural rituals but also carry moral, spiritual, and social messages. Symbols such as siraman (holy bathing), ngabageakeun (welcoming ceremony), saweran (distribution of coins and rice), sungkeman (kneeling gesture of respect), and ngaleupas japati (release of doves) are understood as a medium for conveying values of family life, such as purity, togetherness, respect, and parental blessings. This study employs a qualitative method with a sociological-normative approach, through interviews, observation, and literature review. The findings reveal that these symbols align with Islamic values, particularly in building a sakinah family based on love (mawaddah), mercy (rahmah), and tranquility (sakinah). This study highlights the integration between local Sundanese traditions and Islamic teachings, creating a harmonious framework for cultural preservation and spiritual development. Keywords: wedding symbols, Sundanese culture, sakinah family, adat and Islam